The United Nations and higher education : peacebuilding, social justice and global cooperation for the 21st century - Kester, Kevin (Peace education., 2020)
"In this book, Kevin Kester details how the United Nations promotion of higher education for peace and international understanding sometimes unintentionally contributes to the reproduction of conflict and violence across diverse cultures. He shows this through an in-depth examination of peace curricula, pedagogy and policy in one United Nations higher education institution, where he indicates how dominant philosophical and pedagogical models that signify acceptable peace education ultimately undermine the very goals of educational peacebuilding. Kester contends that theoretical and pedagogical training must develop beyond the dominant psycho-social, rational and state-centric assumptions that permeate the field today if higher education is to better contribute to personal and societal peacebuilding. Drawing from the fields of educational philosophy and sociology, he argues for new concepts of poststructural violence and second order reflexivity that can assist scholars in reducing conflict and building peace in lasting ways. He complements his fieldwork findings with personal reflections throughout the book to reimagine the transformative possibilities of peacebuilding education for the 21st century"--